Development Of Android-Based Application For English Learning System Using Drill and Practice Method - Rohman , Abdur; Diantoro, Karno; Rinaldo; Sitorus, Anwar T.; Juwari (Indonesian Scientific Publication, 2023)
English, being an international language, plays a significant part in daily life worldwide. Many nations utilize English as their primary language of communication. The lack of a novel approach to English learning—such as the use of contemporary technology—means that kindergarteners at Al-Barkah Kindergarten only learn the language through books. In light of these issues, Al-Barkah Kindergarten developed an Android-based application to teach English via the drill and practice method, hence creating a variance in teaching methods. Because this method applies a learning system in the form of visual, audio, and animation that can attract students' interest in learning language, the application design results show that the learning method is effective and that a solution, especially for Al-Barkah Kindergarten students, can easily understand the learning material. English.